Assessing Approaches to Learning in School Readiness - Otilia C. Barbu; David B. Yaden; Deborah Levine-Donnerstein; Ronald W. Marx (SAGE Publishing, 2015)
This study examines the psychometric properties of two assessments of children's approaches to learning: the Devereux Early Childhood Assessment (DECA) and a 13-item approaches to learning rating scale (AtL) derived from the Arizona Early Learning Standards (AELS). First, we administered questionnaires to 1,145 randomly selected parents/guardians of first-time kindergarteners. Second, we employed confirmatory factor analysis (CFA) with parceling for DECA to reduce errors due to item specificity and prevent convergence difficulties when simultaneously estimating DECA and AtL models. Results indicated an overlap of 55% to 72% variance between the domains of the two instruments and suggested that the new AtL instrument is an easily administered alternative to the DECA for measuring children's approaches to learning. This is one of the first studies that investigated DECA's approaches to learning dimension and explored the measurement properties of an instrument purposely derived from a state's early learning guidelines.